The neuroradiology of progressive multifocal leukoencephalopathy: a clinical trial perspective - Baldassari, Laura E.; Wattjes, Mike P; Cortese, Irene C M; Gass, Achim; Metz, Imke; Yousry, Tarek; Reich, Daniel S; Richert, Nancy (Brain, 2022)
Progressive multifocal leukoencephalopathy (PML) is an opportunistic infection of the CNS caused by the JC virus, which infects white and grey matter cells and leads to irreversible demyelination and neuroaxonal damage. Brain MRI, in addition to the clinical presentation and demonstration of JC virus DNA either in the CSF or by histopathology, is an important tool in the detection of PML. In clinical practice, standard MRI pulse sequences are utilized for screening, diagnosis and monitoring of PML, but validated imaging-based outcome measures for use in prospective, interventional clinical trials for PML have yet to be established. We review the existing literature regarding the use of MRI and PET in PML and discuss the implications of PML histopathology for neuroradiology. MRI not only demonstrates the localization and extent of PML lesions, but also mirrors the tissue destruction, ongoing viral spread, and resulting inflammation. Finally, we explore the potential for imaging measures to serve as an outcome in PML clinical trials and provide recommendations for current and future imaging outcome measure development in this area.
Veröffentlicht: 16. November 2021
Gesehen am 12.03.2024